Evaluation of Ophiolite Complex Impact and Pollution Indices of Groundwater Resources in Jovein Area (NE Iran) - Raheleh Hatefi; Morteza Razmara Farzaghi; Seyed Mohammad Zamanzadeh (Journal of Advances in Environmental Health Research)
Background: Potential ore deposits and mining activities can cause soil and groundwater pollution with heavy metals, posing risks to human health. This study aimed to identify heavy metal sources, their transfer patterns, and contamination levels in the Jovein aquifer (NW Sabzevar, Iran).Methods: The groundwater samples were analyzed using inductively coupled plasma mass spectroscopy (ICP-MS). Pollution indices, including the heavy metal pollution index (HPI) and heavy metal evaluation index (HEI), were calculated. Statistical analyses such as principal component analysis (PCA) and cluster analysis (CA) were applied, and results were mapped using ArcGIS software.Results: The average element concentrations followed the order: Boron (B) > chromium (Cr) > barium (Ba) > vanadium (V) > arsenic (As) > aluminum (Al) > lithium (Li) > selenium (Se) > molybdenum (Mo) > copper (Cu) > zinc (Zn) > uranium (U) > tungsten (W) > antimony (Sb). PCA showed Cr and nickel (Ni) originated from weathering of chromite ores and ultramafic rocks, while As and Cu were linked to sulfide mineralization. Although HPI levels were elevated, they remained below critical thresholds. CA grouped samples into two clusters: one with Ni, Cr, and Cu, and the other with As and Sb.Conclusion: Geogenic processes are the main contributors to groundwater contamination, while mining activities have minimal influence in the Jovein aquifer. Overall, the assessment reveals poor groundwater quality due to heavy metal pollution.